Therapeutic plasma exchange for COVID‐19‐associated hyperviscosity. Issue 4 (9th December 2020) - Truong, Alexander D.; Auld, Sara C.; Barker, Nicholas A.; Friend, Sarah; Wynn, A. Thanushi; Cobb, Jason; Sniecinski, Roman M.; Tanksley, Christin‐Lauren; Polly, Derek M.; Gaddh, Manila; Connor, Michael; Nakahara, Hirotomo; et al.
Abstract: Background: Recent data suggests an association between blood hyperviscosity and both propensity for thrombosis and disease severity in patients with COVID‐19. This raises the possibility that increased viscosity may contribute to endothelial damage and multiorgan failure in COVID‐19, and that therapeutic plasma exchange (TPE) to decrease viscosity may improve patient outcomes. Here we sought to share our experience using TPE in the first 6 patients treated for COVID‐19‐associated hyperviscosity. Study Design and Methods: Six critically ill COVID‐19 patients with plasma viscosity levels ranging from 2.6 to 4.2 centipoise (cP; normal range, 1.4‐1.8 cP) underwent daily TPE for 2‐3 treatments. Results: TPE decreased plasma viscosity in all six patients (Pre‐TPE median 3.75 cP, range 2.6‐4.2 cP; Post‐TPE median 1.6 cP, range 1.5‐1.9 cP). TPE also decreased fibrinogen levels in all five patients for whom results were available (Pre‐TPE median 739 mg/dL, range 601‐1188 mg/dL; Post‐TPE median 359 mg/dL, range 235‐461 mg/dL); D‐dimer levels in all six patients (Pre‐TPE median 5921 ng/mL, range 1134‐60 000 ng/mL; Post‐TPE median 4893 ng/mL, range 620‐7518 ng/mL); and CRP levels in five of six patients (Pre‐TPE median 292 mg/L, range 136‐329 mg/L; Post‐TPE median 84 mg/L, range 31‐211 mg/L). While the two sickest patients died, significant improvement in clinical status was observed in four of six patients shortly after TPE. Conclusions: This series demonstrates the utility of TPE to rapidly correct increased blood viscosity in patients with COVID‐19‐associated hyperviscosity. Large randomized trials are needed to determine whether TPE may improve clinical outcomes for patients with COVID‐19.